Fear of disease progression and relapse in multiple sclerosis: a systematic scoping review - Mallahzadeh, Arashk; Fereydoonnezhad, Tahereh; Gauthier, Lynne V.; Farjoud Kouhanjani, Mohsen; Hosseinizadeh, Shima; Khatibi, Ali (Frontiers in Psychiatry, 2025)
BackgroundMultiple sclerosis (MS) is a chronic disease of the central nervous system, most commonly affecting individuals in early adulthood. Uncertainty about future relapses and accumulating disability may lead to significant psychological distress, contributing to reduced quality of life.ObjectiveThis systematic scoping review aimed to synthesize current evidence on the prevalence, determinants, and consequences of fear of relapse and disease progression in people living with MS.MethodThe current systematic scoping review followed PRISMA-ScR guidelines. PubMed, Scopus, and Web of Science were searched from inception until October 6th. Original, English-language studies investigating fear of disease progression or relapse among people with multiple sclerosis were included, without restrictions on age, gender, disease stage, or study design. Data items were collected, and a quality assessment was conducted.ResultsOur search yielded 43 studies, of which 13 met the eligibility criteria. Nine studies utilized the fear of relapse scale and the remaining four used the fear of progression questionnaire. Fear of progression among MS patients ranged from minimal to severe, with concerns centered on losing independence, relying on external help, and potential medication side effects. In relapsing-remitting MS, fear was particularly associated with uncertainty about disease course, potential disability, and worsening fatigue. Increased fear of relapse and progression was strongly associated with higher levels of fatigue, depression, stress, health anxiety, and lower quality of life.ConclusionFear of relapse and progression is common and significantly impacts the lives of people with MS. Future research should focus on evaluating and implementing tailored interventions — including psychological support, educational initiatives, and coping-based strategies — to help patients manage these fears.